2012
DOI: 10.1371/journal.pone.0038707
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Comorbidity on Antihypertensive and Glucose-Regulating Treatment in Diabetes Mellitus – A Cohort Study

Abstract: BackgroundComorbidity is often mentioned as interfering with “optimal” treatment decisions in diabetes care. It is suggested that diabetes-related comorbidity will increase adequate treatment, whereas diabetes-unrelated comorbidity may decrease this process of care. We hypothesized that these effects differ according to expected priority of the conditions.MethodsWe evaluated the relationship between comorbidity and treatment intensification in a study of 11,248 type 2 diabetes patients using the GIANTT (Gronin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
(57 reference statements)
2
29
2
Order By: Relevance
“…That is, that sicker patients with more comorbidity, who will have poorer outcomes, may be less aggressively treated for their diabetes. However, in a previous study we found no evidence that comorbid conditions decrease the likelihood to intensify medication treatment in patients with diabetes [28]. Moreover, the absence of associations between the indicators measuring lipid- and blood pressure-lowering treatment intensification and hard outcomes also makes this explanation less likely.…”
Section: Discussioncontrasting
confidence: 58%
“…That is, that sicker patients with more comorbidity, who will have poorer outcomes, may be less aggressively treated for their diabetes. However, in a previous study we found no evidence that comorbid conditions decrease the likelihood to intensify medication treatment in patients with diabetes [28]. Moreover, the absence of associations between the indicators measuring lipid- and blood pressure-lowering treatment intensification and hard outcomes also makes this explanation less likely.…”
Section: Discussioncontrasting
confidence: 58%
“…Another potential reason for our concordance findings is that patients with more concordant conditions might receive better diabetes care due to a greater sense of urgency in providers and patients to optimize diabetes care for patients who already have diabetic complications and have a greater need for diabetes care goal achievement (American Diabetes Association, 2011; Kerr et al, 2007; Laiteerapong et al, 2011; Voorham et al, 2012). Past studies support this rationale.…”
Section: Discussionmentioning
confidence: 95%
“…Past studies support this rationale. In one study, providers only intensified blood sugar treatment in uncontrolled diabetes for patients who had a new-onset complication (Voorham et al, 2012). In another study, patients with microvascular-concordant conditions expressed higher self-care priority for diabetes care goals than did patients without these concordant conditions (Kerr et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would also be useful to gather information about the duration that the patients have had hypertension to see if that plays a role, which was not done here. Previous studies have shown a relationship between higher blood pressure and higher HbA1c (poorer diabetic health), 26, 27 as well as a relationship between these factors and the presence of both retinopathy and macular edema. 28–30 However, to our knowledge, there is only one other study that examined the relationship between blood pressure and retinal thickness measured by OCT in subjects with diabetes.…”
Section: Discussionmentioning
confidence: 97%